2023
DOI: 10.3389/fimmu.2023.1145552
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of nicotinamide metabolism-related signature for predicting prognosis and immunotherapy response in breast cancer

Abstract: BackgroundBreast cancer (BC) is the most common malignancy among women. Nicotinamide (NAM) metabolism regulates the development of multiple tumors. Herein, we sought to develop a NAM metabolism-related signature (NMRS) to make predictions of survival, tumor microenvironment (TME) and treatment efficacy in BC patients.MethodsTranscriptional profiles and clinical data from The Cancer Genome Atlas (TCGA) were analyzed. NAM metabolism-related genes (NMRGs) were retrieved from the Molecular Signatures Database. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
2
1
0
Order By: Relevance
“…In our OS study, in contrast to the low‐risk group, the high‐risk one presented a notable long‐term survival disadvantage, and it had substantially lower stromal score, immune score, as well as ESTIMATE score, as well as greater responsiveness to a variety of chemotherapeutic agents. These findings were corroborated by previous studies focusing on breast cancer 19,25 . In terms of in vitro OS cell experiments, we demonstrated that by inhibiting the upstream target genes, the TGF‐β1/Smad2/3 pathway can be modulated to promote tumor cell migration, proliferation, as well as invasion, which is consistent with findings in thyroid, 28 gastric, 29 pancreatic, 30 and cervical cancers 31 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our OS study, in contrast to the low‐risk group, the high‐risk one presented a notable long‐term survival disadvantage, and it had substantially lower stromal score, immune score, as well as ESTIMATE score, as well as greater responsiveness to a variety of chemotherapeutic agents. These findings were corroborated by previous studies focusing on breast cancer 19,25 . In terms of in vitro OS cell experiments, we demonstrated that by inhibiting the upstream target genes, the TGF‐β1/Smad2/3 pathway can be modulated to promote tumor cell migration, proliferation, as well as invasion, which is consistent with findings in thyroid, 28 gastric, 29 pancreatic, 30 and cervical cancers 31 .…”
Section: Discussionsupporting
confidence: 90%
“…These findings were corroborated by previous studies focusing on breast cancer. 19,25 In terms of in vitro OS cell experiments, we demonstrated that by inhibiting the upstream target genes, the TGF-β1/Smad2/3 pathway can be modulated to promote tumor cell migration, proliferation, as well as invasion, which is consistent with findings in thyroid, 28 gastric, 29 pancreatic, 30 and cervical cancers. 31 Besides, Zhang et al 32,33 found that glaucocalyxin A and oridonin, both of which can reverse epithelial-mesenchymal transition (EMT) as well as TGF-β3-induced EMT through suppressing TGF-β1/Smad2 in OS, which is an important discovery for innovative drugs of OS.…”
Section: Scrna-seq Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the ROC and calibration curves of the external validation cohort further confirmed the significant predictive value of our model (Figure 2G, H). Taken together, these results demonstrated the outstanding performance of our nomogram compared with previously established prognostic models [43][44][45].…”
Section: Construction and Validation Of A Clinical Nomogramsupporting
confidence: 67%
“…Tian et al have built a prognostic model using basement membrane-related genes 43 . Cui et al have also established a nomogram based on nicotinamide metabolism-related signature 44 , while Li's model was constructed utilizing m6A-related genes 45 . However, none of these models perform better than our PANoptosis-based nomogram (assessed using AUC), further proving the vital value of our research.…”
Section: Discussionmentioning
confidence: 99%